2021
DOI: 10.1007/s13555-021-00548-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Visual Representation of Clinical Efficacy of Ixekizumab in Psoriasis

Abstract: Introduction: Ixekizumab, a high-affinity monoclonal antibody that selectively targets interleukin-17A, is an approved treatment for plaque psoriasis. This study aimed to use animated visualizations as a tool to simplify complex data from ixekizumab clinical trials. Methods: Animated visualizations were developed to show outcomes from ixekizumab clinical trials and a Bayesian network meta-analysis of 11 approved biologics. The visualizations simultaneously highlighted both aggregate scores and the individual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Ixekizumab has shown continued effectiveness in the treatment of psoriasis of the skin and nails. Based on comparison studies with comparative therapies, ixekizumab has shown great significance in treating plaque psoriasis [ 33 ]. In the long-term open-label phases of the psoriasis program, brodalumab was administered to every participant who committed suicide [ 34 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Ixekizumab has shown continued effectiveness in the treatment of psoriasis of the skin and nails. Based on comparison studies with comparative therapies, ixekizumab has shown great significance in treating plaque psoriasis [ 33 ]. In the long-term open-label phases of the psoriasis program, brodalumab was administered to every participant who committed suicide [ 34 ].…”
Section: Reviewmentioning
confidence: 99%
“…Biologics plays an important role in treating this condition [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Table 1 shows important biologics.…”
Section: Present and Future Managementmentioning
confidence: 99%